1996
DOI: 10.1021/bi952012g
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Denaturation of Staphylococcal Nuclease Proline-to-Glycine Substitution Mutants

Abstract: Our recently reported pressure-jump relaxation kinetics experiments on staphylococcal nuclease folding and unfolding [Vidugiris et al. (1995) Biochemistry 34, 4909] demonstrated that both transitions exhibit positive activation volumes, with that of folding being much larger than that of unfolding. Thus high pressure denatures proteins by slowing the rate of folding more than that of unfolding. In the present work, we take advantage of the very slow folding and unfolding rates under pressure to examine the kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
(61 reference statements)
2
37
2
Order By: Relevance
“…However, more recent experimental data (Vidugiris et al, 1996) indicated that the AV~n,l,ing values for H124L and H124L+P117G are identical within experimental error. We calculated the solvent-excluded volumes of H124L and H124L+P117G in the native (X-ray structures) and unfolded (modeled by extended chain) states using the PQMS program by Connolly (1985) ( …”
Section: Lys 116mentioning
confidence: 89%
“…However, more recent experimental data (Vidugiris et al, 1996) indicated that the AV~n,l,ing values for H124L and H124L+P117G are identical within experimental error. We calculated the solvent-excluded volumes of H124L and H124L+P117G in the native (X-ray structures) and unfolded (modeled by extended chain) states using the PQMS program by Connolly (1985) ( …”
Section: Lys 116mentioning
confidence: 89%
“…Activation volumes ⌬v u ‡ and ⌬v f ‡ are derived from a linear fit for pressures between 0 and 500 MPa. (1998) unfolding observed in pressure-jump experiments (41,57,58) suggest that sub-nanosecond molecular-dynamics simulations of pressure denaturation (59-62) do not fully cover the relevant time scales, although an increase in the solvent exposure of residues in the hydrophobic core has indeed been observed in an 800-ps simulation calculation (62). We compared observed activation volumes for folding and unfolding (41) and calculated activation volumes for forming and breaking hydrophobic contacts.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, voids are eliminated by pressure owing to an increase in the population of an alternative packing arrangement of the core in which cavities are filled with native side chains rather than solvent. This model has been suggested to play a role in certain proteins at high pressure (1,(29)(30)(31), although to our knowledge direct observation of structure relaxation under pressure has not been reported.…”
mentioning
confidence: 86%